Does PARP1 up-regulation correlate with PSMA expression in patients with metastatic castration-resistant prostate cancer studied with [18F]PARPi and [68Ga]PSMA PET/CT? - Einspieler, Holger; Ofner, Heidemarie; Ozenil, Marius; Spielvogel, Clemens P; Langrate, Ilva Kristiana; Hassler, Melanie R; Nics, Lukas; Bamminger, Karsten; Baltzer, Pascal A T; Shariat, Shahrokh F; Hacker, Marcus; Kramer, Gero; et al. (European journal of nuclear medicine and molecular imaging, 2025)
PURPOSE: [18F] Poly-ADP-ribose polymerase inhibitors (PARPi), a novel radiotracer, enables visualization of PARP1 upregulation by PET imaging. Here, we aimed to quantify PARPi uptake in tumor lesions of metastatic castration-resistant PCa (mCRPC) patients and perform a comparison with prostate specific membrane antigen (PSMA) expression using PET/CT scans. METHODS: Data from 22 male patients with mCRPC, who underwent [18F]PARPi and [68Ga]Ga-PSMA-11 PET/CT scans, were retrospectively quantified. Lesions with relevant PARPi uptake (higher than background) were delineated and correlated with their [68Ga]PSMA uptake using standardized uptake values (SUV). Additionally, a comparison was performed to investigate the effects of homologous recombination deficiency (HRD) alterations on PARPi tumor uptake. RESULTS: The majority of metastatic PCa lesions that exhibited PARPi uptake were located in the bones (n = 57), with mean SUVmax values of 4.9 ± 1.5 for PARPi and 30.9 ± 28.3 for [68Ga]PSMA. Additionally, 3 local prostate lesions, 14 lymph nodes and 4 further metastatic lesions were detected. Significant correlations were identified between PARPi- and [68Ga]PSMA uptake, as measured by SUVmean (r = 0.48, p < 0.001), SUVpeak (r = 0.48, p < 0.001) and SUVmax (r = 0.43, p < 0.001) of the osseous metastatic lesions and SUVpeak (r = 0.49, p = 0.04) of extraosseous lesions. No significant differences were found between PARPi uptake of metastatic lesions in patients with or without HRD alterations (all p > 0.05). CONCLUSION: Results showed a considerable uptake of [18F]PARPi in mCRPC patients and indicated a correlation between PARPi uptake and PSMA expression, suggesting the potential of using [18F]PARPi as a diagnostic imaging tool in mCRPC patients. More studies are needed to evaluate the clinical benefit of this innovative radiotracer.
Keywords: PET/CT; PSMA; mCRPC; Prostate cancer; 18F-PARPi